Design and development of a smart supermarket system (A) - Lim, Kui Neng (Nanyang Technological University, 2022)
Food wastage has stimulated the interest of governments, international agencies, and researchers from various disciplines in recent years. Concerns about food security and environmental consequences, such as resource depletion and greenhouse gas emissions associated with food waste, have sparked interest in the matter. Individual households have been found to be the primary source of food wastage, even though food wastage happens through the food supply chain. It was observed that household expenditure on groceries increased during the pandemic situation compared to pre-pandemic levels [1]. With food security being a top priority, many have resorted to acquiring and storing additional supplies [2]. As a result of Singapore's government lockdown measures, panic buying and replenishing of a large number of goods and household items have surfaced countrywide [3]. The government had to reassure citizens to shop responsibly by purchasing only what they needed, and supermarket chains had to ramp up shelf replenishment to ensure sufficient supplies to meet growing demand [4]. Such delirious behaviour would lead to the wastage of perishable food items because of poor food consumption habit and planning. This project aims to look at the technologies that could be incorporated in software to assist individuals in making informed food choices in order to address food waste. In addition to being an inventory manager by allowing users to access the expiry dates of registered products, the application further allows users to cook dishes using expiring perishables via the recipe recommender.